2019
DOI: 10.1002/jcla.23063
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of a five‐microRNA signature in breast carcinoma as a promising biomarker for diagnosis

Abstract: Background Breast cancer (BC) is the most common malignancy among females with dismal quality of life in patients. It has been proven that epigenetic factors, especially microRNAs, are involved in breast carcinogenesis and progression. This study aimed to assess the expression and clinical performances of a five‐microRNA signature (miR‐127‐3p, miR‐133a‐3p, miR‐155‐5p, miR‐199b‐5p, and miR‐342‐5p) in breast cancer and adjacent normal tissues to identify a potential biomarker for BC and investigate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…In this study, we successfully established a gefitinib‐resistant cell line (PC9/GR) and found that miR‐133a‐3p was significantly downregulated in the gefitinib‐resistant cell line PC9/GR compared with gefitinib‐sensitive cell line PC9. Previously, miR‐133a‐3p has been reported to be downregulated in many cancers, and low expression of miR‐133a‐3p was associated with tumor recurrence, metastasis, drug resistance, and poor prognosis of cancer patients 32‐34 . Our results also indicate that low expression of miR‐133a‐3p in lung cancer tissues is associated with poor prognosis in patients with lung cancer.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this study, we successfully established a gefitinib‐resistant cell line (PC9/GR) and found that miR‐133a‐3p was significantly downregulated in the gefitinib‐resistant cell line PC9/GR compared with gefitinib‐sensitive cell line PC9. Previously, miR‐133a‐3p has been reported to be downregulated in many cancers, and low expression of miR‐133a‐3p was associated with tumor recurrence, metastasis, drug resistance, and poor prognosis of cancer patients 32‐34 . Our results also indicate that low expression of miR‐133a‐3p in lung cancer tissues is associated with poor prognosis in patients with lung cancer.…”
Section: Discussionsupporting
confidence: 71%
“…Previously, miR‐133a‐3p has been reported to be downregulated in many cancers, and low expression of miR‐133a‐3p was associated with tumor recurrence, metastasis, drug resistance, and poor prognosis of cancer patients. 32 , 33 , 34 Our results also indicate that low expression of miR‐133a‐3p in lung cancer tissues is associated with poor prognosis in patients with lung cancer. Thus, we hypothesized that the downregulation of miR‐133a‐3p expression may support the gefitinib resistance in PC9/GR cells.…”
Section: Discussionsupporting
confidence: 58%
“…Plenty of efforts have been devoted to evaluating the efficacy of miR-133a as a diagnostic marker. By conducting a case-control investigation in 50 pairs of breast cancer and normal tissues, Bitaraf, A. et al considered miR-133a-3p, along with miR-127-3p, miR-155-5p, miR-199b-5p, and miR-342-5p, were promising biomarkers for BC 76 . MiR-133a-3p was significantly modulated in triple-negative breast cancer (TNBC), suggesting that miR-133a-3p might be a predictor of cancer invasion and prognosis 77 .…”
Section: Mir-133a As a Potential Biomarkermentioning
confidence: 99%
“…miR-133a-3p has previously been reported as downregulated in prostate cancer 29 and in other cancer types, including breast 30 , gastric 31 , oesophageal 32 , and colon cancer 33 , suggesting a tumour suppressor function of this miRNA across these cancer types.…”
Section: Discussionmentioning
confidence: 97%